Risk factors for severe COVID-19 in the young—before and after ICU admission - Johanna Kämpe; Olof Bohlin; Martin Jonsson; Robin Hofmann; Jacob Hollenberg; Rebecka Rubenson Wahlin; Per Svensson; Per Nordberg (Annals of Intensive Care, 2023)
Abstract Background Factors associated with severe COVID-19 and death among young adults are not fully understood, including differences between the sexes. The aim of this study was to identify factors associated with severe COVID-19 requiring intensive care and 90-day mortality among women and men below 50 years of age. Methods A register-based study using data from mandatory national registers, where patients with severe COVID-19 admitted to the ICU with need for mechanical ventilation (cases) between March 2020 and June 2021 were matched regarding age, sex, and district of residence with 10 population-based controls. Both the study population and the controls were divided into groups based on age (< 50 years, 50–64, and ≥ 65 years) and sex. Multivariate logistic regression models including socioeconomic factors were used to calculate odds ratios (OR) with 95% confidence intervals (CIs) for associations between severe COVID-19 in the population to compare the magnitude of the risk associations for co-morbidities in the different age categories, and subsequently factors associated with 90-day mortality among patients admitted to ICU. Results In total, 4921 cases and 49,210 controls (median age 63 years, 71% men) were included. The co-morbidities with the strongest associations with severe COVID-19 for the young population compared to older patients were chronic kidney disease (OR 6.80 [3.61–12.83]), type 2 diabetes (OR 6.31 [4.48–8.88]), hypertension (OR 5.09 [3.79–6.84]), rheumatoid arthritis (OR 4.76 [2.29–9.89]), obesity (OR 3.76 [2.88–4.92]), heart failure (OR 3.06 [1.36–6.89]), and asthma (OR 3.04 [2.22–4.16]). When comparing women vs. men < 50 years of age, stronger associations were seen for women regarding type 2 diabetes (OR 11.25 [6.00–21.08] vs OR 4.97 [3.25–7.60]) and hypertension (OR 8.76 [5.10–15.01] vs OR 4.09 [2.86–5.86]). The factors associated with 90-day mortality in the young were previous venous thromboembolism (OR 5.50 [2.13–14.22]), chronic kidney disease (OR 4.40 [1.64–11.78]) and type 2 diabetes (OR 2.71 [1.39–5.29]). These associations with 90-day mortality were foremost driven by the female population. Conclusion Chronic kidney failure, type 2 diabetes, hypertension, rheumatoid arthritis, obesity, heart failure, and asthma were the strongest risk factors associated with severe COVID-19 requiring ICU-care in individuals < 50 years compared to the older population. However, after ICU admission, previous thromboembolism, chronic kidney failure, and type 2 diabetes were associated with increased 90-day mortality. The risk associations for co-morbidities were generally stronger among younger individuals compared to older and in women compared to men.